Frequency of Iron Deficiency in Heart Failure Patients - Muhammad Qasim, Bushra Anwar, Amir Qureshi, Muazam Ali Shehzad, Syed Imran Ahmed Kazmi, Ayesha Bibi (Pakistan Journal of Medical & Health Sciences, 2023)
Background: People suffering from heart failure frequently face iron deficiency, which has been linked to higher mortality and more frequent hospital stays. People with symptomatic systolic heart failure and iron deficiency, iron supplementation significantly decreased the risk of hospitalization for heart failure and the combined endpoint of hospitalization for heart failure and mortality, Aim: This research sought to determine the prevalence of iron insufficiency in people with chronic heart failure. Design of the study: This study is cross-sectional. Place of the study: Ayub Teaching Hospital Abbottabad from November 2019 to April 2020. Methodology: After obtaining written informed permission, the research participants who met the inclusion criteria were chosen. Patients between the ages of 40 and 70, of either gender, were included in the research group if they had a documented history of CHF for less than six months and an echocardiogram showed an LVEF of less than 45%. Results: Mean age of the patients was 55.79±9.926, ranging from 40 to 70 years and the mean BMI was 29.03±5.043 ranging from 19 to 49kg/m2, mean serum ferritin level was 226.03±160.297 ranging from 70 to 500μg/L and mean transferrin saturation was 23.15±6.449 ranging from 15 to 38%. In the frequency of heart failure, patients of heart failure were 72(48%) and 78(52%) had no HF. In the frequency of iron deficiency, patients found with a deficiency were 82(54.7%) and 68(45.3%) had no deficiency. Practical Implication: Patients with heart failure should have routine iron deficiency screenings regardless of the presence of anaemia or abnormal RCI. In order to improve risk-based selection of participants who are frequently not at risk for iron deficiency Conclusion: Men with functional classes II–III were more likely to have iron deficiency anaemia (72% prevalence). Hypertension was the most prevalent comorbidity. Keywords: Iron deficiency, Heart failure, Anemia